How to cool lithium ion batteries: optimising cell design using a thermally coupled model - Zhao,Y; Diaz,LB; Patel,Y; Zhang,T; Offer,GJ (Journal of The Electrochemical Society, 2019)
Cooling electrical tabs of the cell instead of the lithium ion cell surfaces has shown to provide better thermal uniformity within the cell, but its ability to remove heat is limited by the heat transfer bottleneck between tab and electrode stack. A two-dimensional electro-thermal model was validated with custom made cells with different tab sizes and position and used to study how heat transfer for tab cooling could be increased. We show for the first time that the heat transfer bottleneck can be opened up with a single modification, increasing the thickness of the tabs, without affecting the electrode stack. A virtual large-capacity automotive cell (based upon the LG Chem E63 cell) was modelled to demonstrate that optimised tab cooling can be as effective in removing heat as surface cooling, while maintaining the benefit of better thermal, current and state-of-charge homogeneity. These findings will enable cell manufacturers to optimise cell design to allow wider introduction of tab cooling. This would enable the benefits of tab cooling, including higher useable capacity, higher power, and a longer lifetime to be possible in a wider range of applications.